Surface antigen serocleared hepatitis B virus infection increases the risk of mixed cryoglobulinemia vasculitis in male patients with chronic hepatitis C - Morrone, Anna; Fiorilli, Valerio; Cinti, Lilia; Roberto, Piergiorgio; Ferri, Alejandro L.; Visentini, Marcella; Pulsoni, Alessandro; Spinelli, Francesca Romana; De Santis, Adriano; Antonelli, Guido; Basili, Stefania; Tosti, Maria Elena; et al. (Frontiers in Immunology, 2024)
Mixed cryoglobulinemia vasculitis (MCV) is caused in ~90% of cases by chronic hepatitis C virus (HCV pos MCV) and more rarely by hepatitis B virus (HBV) infection, or apparently noninfectious.HCV pos MCV develops in only ~5% of patients with chronic hepatitis C (CHC), but risk factors other than female gender have not been identified so far. We conducted a retrospective case control study investigating whether past active HBV infection, defined by hepatitis B surface antigen (HBsAg) seroclearance and anti-core antibody (HBcAb) positivity, could be a risk factor for developing HCV pos MCV. The prevalence of HBsAg seroclearance was 48% within 123 HCV pos MCV patients and 29% within 257 CHC patients (p=0.0003). Multiple logistic regression including as variables gender, birth year, age at HBV testing, cirrhosis, and hepatocellular carcinoma, confirmed an association of HBsAg seroclearance with HCV pos MCV [adjusted odds ratio (OR) 2.82, 95% confidence interval (95% CI) 1.73-4.59, p<0.0001]. Stratification by gender, however, showed that HBsAg seroclearance was associated with HCV pos MCV in male [OR 4.63, 95% CI 2.27-9.48, p<0.0001] and not in female patients [OR 1.85, 95% 95% CI 0.94-3.66, p=0.076]. HBsAg seroclearance, and more likely occult HBV infection, is an independent risk factor for HCV pos MCV in male CHC patients.